Putting the state in its place: The critique of state-centrism and its limits - Lacher, H (Cambridge Univ Press, 2003)
The critique of state-centrism is a crucial aspect of the restructuring of International Relations theory, widely seen as a precondition for the conceptualisation of international transformation. In this article, I argue that the terms on which this critique is framed lead to claims which are both too sweeping in their implications for a transformation to a post-Westphalian system, and not radical enough with respect to the Westphalian period itself. The critique of state-centrism is premised on the assumption that modernity was a territorial order in which states contained 'their' societies. But modern social relations always included global dimensions. If the modern social sciences discounted these global aspects of modernity, the way forward for the social sciences, and IR in particular, cannot be in embracing the notion of a contemporary shift from the national to the global, but in a reconsideration of modernity itself Just as the new globalism is inadequate as a basis for understanding our supposedly postmodern times, so nation-statism was always defective as a basis for understanding modernity. I argue that the notion of a national/global dialectic provides a better basis for understanding the current socio-spatial transformation.
Keywords: International Political-Economy; Marxism